Nitrogen Deposition Shifts Grassland Communities Through Directly Increasing Dominance of Graminoids: A 3-Year Case Study From the Qinghai-Tibetan Plateau - Shen, Hao; Dong, Shikui; DiTommaso, Antonio; Xiao, Jiannan; Lu, Wen; Zhi, Yangliu (Frontiers in Plant Science, 2022)
Nitrogen (N) deposition has been increasing for decades and has profoundly influenced the structure and function of grassland ecosystems in many regions of the world. However, the impact of N deposition on alpine grasslands is less well documented. We conducted a 3-year field experiment to determine the effects of N deposition on plant species richness, composition, and community productivity in an alpine meadow of the Qinghai-Tibetan Plateau of China. We found that three years of N deposition had a profound effect on these plant community parameters. Increasing N rates increased the dominance of graminoids and reduced the presence of forbs. Species richness was inversely associated with aboveground biomass. The shift in plant species and functional group composition was largely responsible for the increase in productivity associated with N deposition. Climatic factors also interacted with N addition to influence productivity. Our findings suggest that short-term N deposition could increase the productivity of alpine meadows through shifts in composition towards a graminoid-dominated community. Longer-term studies are needed to determine if shifts in composition and increased productivity will be maintained. Future work must also evaluate whether decreasing plant diversity will impair the long-term stability and function of sensitive alpine grasslands.